2017
DOI: 10.4012/dmj.2016-334
|View full text |Cite
|
Sign up to set email alerts
|

Resin adhesion strengths to zirconia ceramics after primer treatment with silane coupling monomer or oligomer

Abstract: Resin bonding to zirconia ceramics is difficult to achieve using the standard methods for conventional silica-based dental ceramics, which employ silane coupling monomers as primers. The hypothesis in this study was that a silane coupling oligomer -a condensed product of silane coupling monomers-would be a more suitable primer for zirconia. To prove this hypothesis, the shear bond strengths between a composite resin and zirconia were compared after applying either a silane coupling monomer or oligomer. The she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…When the experimental novel silane agent is initiated by aqueous hydrochloric acid, the C-H groups in ≡Si-O-CH 3 (or ≡Si-O-CH 2 CH 3 ) become significantly weaker, while the ≡Si-OH group becomes stronger and, finally, a very strong -Si-O-Zr group appears. 35 These results indicate that hydrochloric acid effectively promotes the hydrolysis of 3-MPTS, resulting in the adherence of hydrolyzed 3-MPTS to the ceramic surface by chemical bonds. The SEM observation (Figure 5(b)) reveals that air-particle abrasion with alumina particles is a suitable zirconia surface treatment method for increasing the surface energy of ceramics and the wettability between resins and ceramics.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…When the experimental novel silane agent is initiated by aqueous hydrochloric acid, the C-H groups in ≡Si-O-CH 3 (or ≡Si-O-CH 2 CH 3 ) become significantly weaker, while the ≡Si-OH group becomes stronger and, finally, a very strong -Si-O-Zr group appears. 35 These results indicate that hydrochloric acid effectively promotes the hydrolysis of 3-MPTS, resulting in the adherence of hydrolyzed 3-MPTS to the ceramic surface by chemical bonds. The SEM observation (Figure 5(b)) reveals that air-particle abrasion with alumina particles is a suitable zirconia surface treatment method for increasing the surface energy of ceramics and the wettability between resins and ceramics.…”
Section: Discussionmentioning
confidence: 79%
“…As a result, some incompletely hydrolyzed 3-MPTS molecules are adsorbed physically on the ceramic surface, competitively occupying the Zr-O positions on the ceramic surface and hindering the formation of Zr-O-Si bonds. 3335 For example, the carbonyl groups of 4-methacryloxyethyltrimelliticacidanhydride (4-META) are bonded to the silanol groups on the ceramic surface by hydrogen bonding, which hinders the chemical adsorption of 3-MPTS molecules, thus leading to a reduction in their condensation efficiency. This effect influences the bonding strength between the zirconia ceramic surface and composite resin.…”
Section: Discussionmentioning
confidence: 99%
“…FT-IR results confirmed that the silane was bound to the surface of the radiopacifiers, similar to other studies using the same silane (MPS) and similar protocols to effectively coat titanium dental implants and yttria-stabilised zirconium ceramics. 61,62 The higher thermal conductivity of TiO 2 did not drastically alter the setting properties and heat dissipation of bone cement. Higher levels of metal oxide fillers ('40%w/w) may be required to observe such an effect as reported in the literature.…”
Section: Discussionmentioning
confidence: 92%
“…FT-IR results confirmed that the silane was bound to the surface of the radiopacifiers, similar to other studies using the same silane (MPS) and similar protocols to effectively coat titanium dental implants and yttria-stabilised zirconium ceramics. 61,62…”
Section: Discussionmentioning
confidence: 99%
“…The major clinical problem with the use of zirconiabased ceramics is the difficulty in achieving suitable bonding to luting agents [28][29][30] or veneering/glazing ceramics 31,32) . The presence of SiO2 on the coating layer would be preferable to achieve suitable bonding to luting agents/primers containing silane coupling agents and also to silica based veneering/grazing ceramics.…”
Section: Discussionmentioning
confidence: 99%